Transformations of Meaning in B. Okudzava’s Poetry in Polish Translations by E. Cheh - Mazur-Mierzwa, Lidia (Respectus Philologicus, 2024)
The present research deals with some questions about translating B. Okudzava’s poetry into Polish. It is emphasised that any translation is affected by the providing and receiving culture, and a translator, while translating, takes a special place in the creative act because s/he is the recipient of the original text.The article focuses on a well-known Polish translator, E. Cheh’s translations. He translated Okudzava and other famous Russian authors (e.g., Solzhenitsyn, Stroganov, Koliada, Vysotsky, etc.). The article attempts to answer the question of how the translation modifies under the influence of different factors. Expression depends on the peculiarities of the translator’s understanding and how being culturally determined also influences the translation.Translation transformations in E. Cheh’s creation tend to be of replacement and addition. Elimination is less significant.Transformations of meaning in translations are less or more determined by the translator’s cultural peculiarities of a certain national cognitive space.